Contesting liberal-colonial citizenship: the planetary model of citizenship and the struggle for the ‘right to shelter’ - Peeck-Ho, Catharina; Bös, Mathias (Frontiers in Sociology, 2025)
Anti-immigrant mobilization has reached a new peak with the rise of right-wing neo-fascist movements and many problems in contemporary societies are discursively linked to immigration. These developments pose new challenges to the ongoing struggle for immigrants’ rights, as current discourses on so-called “sanctuary cities” in the United States demonstrate. The article makes the case that these phenomena are connected to different knowledge orders about citizenship and its underlying principles. While the liberal nation-state is based on the idea of the equality and national sovereignty, new social movements have fundamentally problematized global social inequalities and injustices. Their visions are not only about equality between humans, but include a different understanding of society’s relationship with nature. In this article, we argue that the normative foundations and knowledge orders associated with these issues are accompanied by different—and sometimes incompatible—models of citizenship, which can be typified as ‘liberal-colonial citizenship’ and ‘planetary citizenship’. They imply different notions of belonging and social justice and emphasize different forms of rights (e.g., citizenship rights vs. human rights). An analysis of current discourses on the so-called ‘right to shelter’ law in Massachusetts shows how different models of citizenship are applied to legitimize political claims, suggesting either an inclusive model for dealing with immigration or excluding non-citizens. The paper shows how the legal and administrative inclusion of immigrants reflects contested knowledge orders about the content and normative basis of citizenship within these struggles.